2021
DOI: 10.1038/s41467-021-25738-6
|View full text |Cite|
|
Sign up to set email alerts
|

Neutral bots probe political bias on social media

Abstract: Social media platforms attempting to curb abuse and misinformation have been accused of political bias. We deploy neutral social bots who start following different news sources on Twitter, and track them to probe distinct biases emerging from platform mechanisms versus user interactions. We find no strong or consistent evidence of political bias in the news feed. Despite this, the news and information to which U.S. Twitter users are exposed depend strongly on the political leaning of their early connections. T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
24
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4
1

Relationship

3
7

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 59 publications
7
24
0
2
Order By: Relevance
“…Action is needed especially because our audit found more biases among right-leaning users and our intervention showed that it takes considerably more effort to debias YouTube recommendations for these users as well (see also [113] for similar biases on Twitter, where right-leaning accounts did not experience exposure to moderate information and produced increasingly partisan content, partly due to bots and social networks). Although these right-wing biases are not very pronounced, they are there, detected, and visible.…”
Section: Discussionmentioning
confidence: 90%
“…Action is needed especially because our audit found more biases among right-leaning users and our intervention showed that it takes considerably more effort to debias YouTube recommendations for these users as well (see also [113] for similar biases on Twitter, where right-leaning accounts did not experience exposure to moderate information and produced increasingly partisan content, partly due to bots and social networks). Although these right-wing biases are not very pronounced, they are there, detected, and visible.…”
Section: Discussionmentioning
confidence: 90%
“…In terms of content, malicious bots are found to engage other accounts with negative and inflammatory language [11] or hate speech [30,17]. In some cases, bots form dense social networks to boost engagement and popularity metrics and to amplify each other's messages [31,32,33].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, on social media platforms, false information is typically shared by more users, and travels far more rapidly than reliable information [19]. This condition is further exacerbated by the presence of social bots [20,21] -i.e., automated accounts impersonating humans -that act as magnifiers of noise, conflicts and (mis)information spread [22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%